Preservation of minimally processed aurora-1 peaches using additives - Martins, Ramilo Nogueira [UNESP]; Mattiuz, Ben-Hur [UNESP]; Santos, Leandra Oliveira [UNESP]; Ascari Morgado, Cristiane Maria [UNESP]; Machado Mattiuz, Claudia Fabrino [UNESP] (Soc Brasileira Fruticultura, 2011)
'Aurora-1' peaches establishes an interesting alternative as a minimally processed product, due to its characteristics like flavor, color, smell, and also because of its handling resistance. However, it has a short shelf life after a fresh-cut due to enzymatic browning and stone cavity collapse. The main purpose of this research was to test the additive with antioxidant effect to prevent browning in minimally processed 'Aurora-1' peaches. The minimal processing consists of washing, sanitizing, peelings and fruit stone extraction. After that, longitudinal cuts were made to obtain eight segments per fruit. The slices were immersed into the following treatment solutions: control (immersion in 2% ascorbic acid); 2% ascorbic acid + 2% calcium chloride; 1% sodium isoascorbate; 1% citric acid; 1% L-cysteine hydrochloride. The products were placed into rigid polystyrene trays branded MEIWA M-54, covered with 14 mu m PVC film (Omnifilm (TM)) and kept in cold storage at 3 degrees C +/- 2 degrees C and 65% RH for twelve days, and evaluated each three days. Appraised variables were appearance, soluble solids, titratable acidity, soluble carbohydrates and reducing sugars, total and soluble pectin, ascorbic acid, and peroxidase and polyphenol oxidase enzyme activity. L-cysteine gave to the minimally processed products a shelf life of twelve days, limmited by off-flavor. The treatment with ascorbic acid was efficient to maintainthe ascorbic acid content, with a shelf-life of nine days, limited by enzymatic browning.

O pêssego 'Aurora 1' constitui interessante alternativa como produto minimamente processado, devido principalmente às suas características de sabor, coloração, aroma e também por ser uma fruta resistente ao manuseio. No entanto, possui curta vida de útil após o processamento mínimo devido ao escurecimento enzimático e ao colapso da cavidade do caroço. Objetivou-se, neste trabalho, a avaliação de aditivos com efeito antioxidante na prevenção do escurecimento de pêssegos 'Aurora-1', minimamente processados. O processamento mínimo consistiu de lavagem, sanificação, descasque e retirada do caroço das frutas. Em seguida, realizaram-se cortes longitudinais para obtenção de oito segmentos por fruto. As fatias obtidas foram imersas nas soluções, compondo os tratamentos: testemunha (imersão em ácido ascórbico a 2%); ácido ascórbico a 2% + cloreto de cálcio a 2%; isoascorbato de sódio a 1%; ácido cítrico a 1%; cloridrato de L-cisteína a 1%. Foram acondicionadas em bandejas de poliestireno, rígidas, marca MEIWA M-54, revestidas com filme de PVC esticável de 14µm (Omnifilm®), armazenados em câmara fria a 3ºC ± 2ºC e 65% UR por 12 dias e avaliados a cada três dias. As variáveis avaliadas foram aparência, sólidos solúveis, acidez titulável, relação sólidos/acidez, açúcares solúveis e redutores, pectina total e solúvel, ácido ascórbico, atividade das enzimas peroxidase e polifenoloxidase. A L-cisteína proporcionou aos produtos minimamente processados vida útil de 12 dias, sendo limitada pelo odor não característico do produto. O ácido ascórbico mostrou-se eficiente na manutenção do ácido ascórbico, com vida útil de nove dias, sendo limitado pelo escurecimento enzimático.
Uso de aditivos para consevarção de pêssegos aurora-1 minimamente processados
Keywords: ascorbic acid; calcium chloride; Cysteine; citric acid; isoascorbate